Analisis Tingkat Kemandirian Keuangan Pemerintah Daerah Kota Batam untuk Tahun 2006-2010 - Irsutami Irsutami (Politeknik Negeri Batam, 2013)
Financial autonomy will assist to implementation of regional autonomy, but the natural resources factor can acceleration it and Batam is potential reliaze that., thus research is needed to describe financial autonomy degree. The research was conducted in Government of Batam District with the period analisys is 2006 - 2010. Interviews and inspection several of data is done and using descriptive analysis method. The results of researceh showed that the level of financial autonomy Government of Batam District is still below 25% for the years 2006 to 2010 with the degree of fiscal decentralization between 10.1% - 20% which means that the Batam PAD are still less reliable for the operational governance and other expendutures.